bahasa inggris - Khoiryah, Yeni Ayu; Risnita; Sastradika, Dedi; Sakunti, Sri Ramdayeni (Al-TA'DIB: Jurnal Kajian Ilmu Kependidikan, 2026)
This study was motivated by concerns that Islamic Religious Education (PAI), particularly Qur'an and Hadith learning, continues to emphasize memorization rather than Higher-Order Thinking Skills (HOTS). It aimed to develop and validate a HOTS-based assessment instrument for senior high school students. Using a Research and Development (R&D) approach with the ADDIE model, 35 HOTS-based items were developed, validated by five experts, and tested on 308 students. Data were analyzed using Aiken's V and the Rasch Model through QUEST software. The instrument achieved an average Aiken's V of 0.88, indicating very high content validity. Rasch analysis showed excellent item reliability (0.99) and moderate person reliability (0.67), while identifying several items requiring revision. After refinement, the instrument demonstrated acceptable psychometric properties, providing a valid and reliable assessment tool to measure students' analytical, evaluative, and reflective skills in Qur'an and Hadith learning.